The Impact and Effects of Financial Reporting in the Public Accounting Econometric Analysis Model: Revenue and Expenditures for Period 2007-2017 - Enkeleda, Lulaj (European Journal of Economics and Business Studies, 2019)
This scientific paper it aims to look at the importance and effects of financial reporting in public accounting by analyzing incomes (receipts) and expenditures (payments) in the money cash during the period 2007-2017. The impact and effects of globalization and the numerous changes in various economic activities, in particular financial reforms in transition countries with particular emphasis on the state of Kosovo, added the need for application and harmonization of accounting standards and financial reporting standards. The importance of applying these standards is to increase the importance and effects on financial reforms by applying a set of uniform and rigorous rules for financial reporting in the annual, nine-month, six-month, quarterly, and monthly financial statements. Thus, the purpose of this scientific paper is the ecometric analysis of financial statements for receipts and payments based in the cash money ,which include public revenue and public expenditures during the 10 year period ,using statistical analysis and tests such as: regression, anova, t-test, intercept, degree of freedom, multiple R, square R, F, and others models that coincide this research for each variable, proving hypotheses or not, how important and what have been the effects on financial reforms during 2007-2017. Findings from this research will be help the state of the Kosovo look at financial reforms and comparability between the years for each variable.